Enzymatic hydrolysate of porphyra enhances the intestinal mucosal functions in obese mice. Issue 8 (4th May 2022) - Li, Chunjun; Cheng, Xiaojie; Cao, Wanxiu; Wang, Yuming; Xue, Changhu; Tang, Qingjuan
Abstract: Intestinal mucosal immunity is important to human body; however, obesity induced by high‐fat diet may bring a series of problems, such as chronic inflammation which may damage intestinal mucosal immunity. In this study, the effects of two different enzymatic hydrolysates of porphyra on the function of intestinal mucosal were explored in obese mice. The results showed that 10 consecutive weeks of high‐fat dietary intake resulted in weight gain and intestinal abnormalities in C57BL/6 mice. However, the administration of enzymatic hydrolysate of porphyra effectively protected the intestinal mucosa from these injuries while reducing levels of oxidative stress (MDA, GSH, and GSH‐Px). Specifically, they were found to improve small intestine morphological structure, increase growth of goblet cells and mucous, raise expression levels of lysozyme, and stimulate SIgA secretion, especially in the group administered with the enzymatic hydrolysate containing protease and polysaccharide enzyme (EHPP). The results showed that the enzymatic hydrolysates of porphyra may provide a protective measure to maintain intestinal mucosal barriers, which is beneficial to overall health. Porphyra is widely distributed all over the world. Moreover, an increasing number of studies have described its diverse biological functions. Therefore, it is necessary to find a way to develop products related to porphyra. In this study, a new type of polysaccharide enzyme of porphyra found in our previous research was used to make a clear porphyra energy drink with a lower molecular weight polysaccharide. Our findings highlighted the repaired intestinal barriers in obese bodies after the treatment with the enzymatic hydrolysate. Practical applications: Porphyra is widely distributed all over the world. Moreover, an increasing number of studies have described its diverse biological functions. Therefore, it is necessary to find a way to develop products related to porphyra. In this study, a new type of polysaccharide enzyme of porphyra found in our previous research was used to make a clear porphyra energy drink with a lower molecular weight polysaccharide. Our findings highlighted the repaired intestinal barriers in obese bodies after the treatment with the enzymatic hydrolysate. Abstract : Enzymatic hydrolysate of porphyra has protective effects on intestinal mucosal dysfunction in obese mice.